2009
DOI: 10.1007/s10573-009-0005-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of agglomeration during combustion of aluminized solid propellants in an acceleration field

Abstract: Agglomeration during combustion of solid rocket propellants in an acceleration field up to 60 was studied experimental. In the experiments, the acceleration direction and magnitude were varied. The amount, chemical composition, and particle size of the agglomerates and the structure of the surface layer were determined as functions of the acceleration magnitude and direction. The most significant feature of the effect of tensile accelerations is an increase in the agglomerate mass to a certain limiting value, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The mass of metal of agglomerates in conditions of tensile accelerations grows, reaching some limit- ing value. This is because accelerations a¨ect on duration of evolution process [40]. As a result of the evolution on the surface of burning propellant, the agglomerates of di¨erent types are formed.…”
Section: Solid and Hybryd Propulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass of metal of agglomerates in conditions of tensile accelerations grows, reaching some limit- ing value. This is because accelerations a¨ect on duration of evolution process [40]. As a result of the evolution on the surface of burning propellant, the agglomerates of di¨erent types are formed.…”
Section: Solid and Hybryd Propulsionmentioning
confidence: 99%
“…If tensile accelerations exceed some limiting value, then duration of evolution is negligible, and chemical composition of agglomerates corresponds to the ratio between metal and oxide in the SL. It is shown that in the absence of accelerations, up to 25 %(mass) of metal in agglomerating particles burn in gas-phase mode at their evolution [40]. Thus, it was assumed that at zero accelerations, evolution duration at realization of the ¤pocket¥ mechanism is determined by the time needed for burnout of 25 %(mass) of metal.…”
Section: Solid and Hybryd Propulsionmentioning
confidence: 99%
“…xtOkt "1 VRwU MQv Q}}eD [3] "CU= xOW |UQQ [10] " ?=DW QF= QO j= QDL= |x}L=v |R=o R=i uOW sm = QDt x@ OQ=wt |NQ@ QO w [17] Ov=xOv=t |xv= QW}B l} VRwU |OOa |R=Ux}@W Qw_vt u}O@ [18] "CU= xOW xO=O C@Uv |Dw=iD x@ xHwD=@ [19]…”
mentioning
confidence: 99%